The Effect of Bacillus thuringiensis toxin Cry1A.105 and Cry2Ab2 on The Survival of The Non-Target Pest, Spodoptera litura - Kurnia Pratiwi; Y. Andi Trisyono; Edhi Martono (Jurnal Perlindungan Tanaman Indonesia, 2016)
Spodoptera litura is one of the important insect pest of maize besides the notoriously damaging corn borer, Ostrinia furnacalis. S. litura has been the target of various controls including the use of Bacillus thuringiensis (Bt) toxin Cry1A.105 and Cry2Ab2. This study was conducted to evaluate the acute effect of Bt toxin Cry1A.105 and Cry2Ab2 on the growth and development of S. litura from larval to adult stages. Two sublethal concentrations were used; 0.1875 and 0.0469 ppm for Cry1A.105, and 0.0008 and 0.0003 ppm for Cry2Ab2. The bioassay using diet dipping was carried out on a CRD with three experiments and five repetitions. The observation was carried out on the mortality and survival rates of S. litura. The mortality reached 28% when the larvae were treated with 0.1875 ppm and 20% with 0.0469 ppm of Cry 1A.105. The exposed larvae and pupae were smaller than control. Larval and pupal weight were 117.0 and 165.6 g with 0.1875 ppm, while control were 212.9 and 211.2 g. Cry1A.105 also longer the larval stage, larval stage with higher and lower concentration were 24.5 and 22.3 day, while control was 20.5 day. The resulted pupae from larve which exposed by Cry1A.105 were less than control; there were 40% at concentration 0.1875 ppm and control 61%. The two concentration of Cry2Ab2 produced similar mortality of 20%. Similarly, Cry2Ab2 affected pupal to adult stages development. The longevity of pupal stage with concentration 0.0003 ppm was 9.5 days, followed by 0.0008 ppm (9.1 days) and control (10.1 days). The adult emerge on the highest concentration was 47.4% while control only 34.6%. There results showed that both Cry1A.105 and Cry2Ab2 were detrimental to the survival of S. litura which is the non-target insect of transgenic Bt maize.